Stepwise contraction of the nf Rydberg shells in the 3d photoionization of multiply-charged xenon ions. (August 2015) - Schippers, S; Borovik, A; Buhr, T; Hellhund, J; Holste, K; Kilcoyne, A L D; Klumpp, S; Martins, M; Müller, A; Ricz, S; Fritzsche, S
Synopsis: Photoionization of Xe 3+, Xe 4+ and Xe 5+ ions was measured in the energy range 670-750 eV, including the 3 d ionization threshold. The cross sections exhibit a progressively larger number of sharp resonances as the ion charge state is increased. This clearly visualizes the re-ordering of the εf continuum into a regular series of (bound) Rydberg orbitals as the ionic core becomes more attractive.